The influence of social support on improving the quality of life and nutritional status of tuberculosis patients - Prabowo, Anis; Sudargo, Toto; Triasih, Rina (Edelweiss Applied Science and Technology, 2026)
Tuberculosis (TB) remains a major global health challenge, substantially impairing patients’ quality of life (QoL) and nutritional status. Although social support is an essential component of TB care, the specific impact of peer support delivered by TB survivors has not been adequately explored. A quasi-experimental study with a non-equivalent control group and pretest–posttest design was conducted among 76 patients with pulmonary TB. Participants were assigned to an intervention group receiving structured mentoring from trained TB survivors or a control group receiving standard care. QoL was assessed using the Short Form-36, while nutritional status was evaluated through body weight and BMI. The intervention group demonstrated significantly greater improvements in overall QoL compared with the control group (mean score 80.72 vs. 71.43; p<0.001), particularly in social functioning, vitality, and mental health domains, nutritional outcomes also improved more markedly in the intervention group, with higher mean weight gain (6.33 kg vs. 4.48 kg; p=0.001) and a greater increase in BMI (from 19.85 to 22.26). Peer-based social support provided by TB survivors effectively improves both QoL and nutritional status among patients undergoing TB treatment. Integrating survivor-led mentoring into routine TB care may promote a more holistic and patient-centered recovery approach.